Uses and gratification of spiritual and religious music in Egypt: A descriptive analysis study - El-Taher, Hend (AUC Knowledge Fountain, 2017)
Media is one important constituent of the culture in a society. Its importance is reflected in the contents it presents especially in religion and music. The way both religion and music are blended and used as a medium to gratify certain needs is the interest of this study. In that sense, the relation between religions and music is examined, how music was perceived by religious figures, what disputes the music provoked, and how spiritual music is used as an intrapersonal, interpersonal, or a mass communication tool to influence the audience cognitively, behaviorally, and attitudinally. Accordingly, a descriptive survey is conducted on a purposive sample in six academic institutes in Egypt, the American University in Cairo, the British University in Egypt, the German University in Cairo, Cairo University, Ain Shams University, and Al-Azhar University. The Uses and Gratifications theory and the Social Identity Theory helped to interpret the data that were collected from 383 respondents. Based on the results, 66.8% of 337 participants highly use spiritual and religious music as an emotional therapy. However, using the medium as an emotional therapy did not encourage cultural activities such as attending concerts, buying or selling related products, and reading books.